Analysis of capital buffers in Serbia - Vesna Martin (Anali Ekonomskog fakulteta u Subotici, 2021)
The aim of this paper is to analyse all capital buffers that are currently applied in Serbia. Regulation that transposes Basel III regulatory standards in Serbia was adopted in December 2016. These buffers increase the resilience of banks to losses, reduce excessive or underestimated exposures and restrict the distribution of capital. An assessment of the long-term trend of the credit-to-GDP ratio is based on using a one-sided Hodrick-Prescott filter and the selected value of the parameter λ equals 400000. Also, this paper used the following methods of research: inductive and deductive methods, methods of analysis and synthesis, classification method and the method of comparison. Analysis has shown that capital buffers that are currently applied in Serbia are fully harmonized with European Union regulations and international best practices.